Preparation method of high-selectivity functionalized ZIF-7-8 mixed matrix membrane
By introducing ZIF-7-8 and ionic liquid into the membrane material, combined with hybrid zeolite imidazole ester framework material, a highly selective functionalized hybrid matrix membrane was prepared, which solved the shortcomings of existing membrane materials in CO2/N2 selectivity and achieved efficient gas separation effect.
Patent Information
- Application Number
- CN202411826938.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
Existing membrane materials have shortcomings in carbon dioxide and nitrogen selectivity, making it difficult to achieve efficient CO2/N2 gas separation.
The metal organic framework ZIF-7-8 with carbon dioxide adsorption properties was introduced through blending technology, and the ionic liquid 1-butyl-3-methylimidazole bistrifluoromethanesulfonimide salt ([bmim][Tf2N]) was used for post-synthesis treatment. Combined with hybrid zeolite imidazole ester framework material, a highly selective functionalized ZIF-7-8 hybrid matrix membrane was prepared.
The selectivity of the membrane to CO2/N2 is significantly improved, and efficient gas separation is achieved. The preparation process is gentle and simple, and the cost is low.
Smart Images

Figure CN119607894A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas separation materials, in particular to a method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane. Background Art
[0003] Compared with traditional gas separation technology, membrane separation technology has the advantages of easy operation, low energy consumption, and no pollution. It is considered to be the most promising third-generation separation technology and has received widespread attention from all walks of life. Among the many membrane materials, organic membranes have been widely studied due to their advantages such as low cost, easy availability, and large-area membrane production. However, it is difficult for such materials to overcome the mutual constraints between permeability and selectivity (the "trade-off" effect), and the performance of the membrane is usually limited below the Robeson upper bound. Inorganic membranes have excellent separation performance, thermal stability, and chemical stability, and have always been a hot topic in membrane technology research. However, high cost and fragile preparation have hindered the further development of inorganic membranes. In order to solve these problems, researchers have tried to combine the advantages of low cost and easy film formation of polymer membranes with the advantages of high performance of inorganic membranes, so as to prepare mixed matrix membranes with better performance.
[0004] In mixed matrix membranes, the properties of fillers play a decisive role in the gas separation performance of membrane materials. Therefore, the selection of fillers is crucial in the preparation process of mixed matrix membranes. First, the selected filler particle size should not be too large. Selecting micro-fillers with nanometer size can ensure that the fillers are well distributed in the free volume between the polymer chains, and then have a certain impact on the stacking of the molecular chains, which is conducive to regulating the free volume of the membrane material, thereby improving the gas transmission performance. At the same time, the nanometer-scale filler has a certain pore filling effect in the free volume with large permeability, which hinders the penetration of large-sized gas molecules, thereby improving the selectivity of the gas. At the same time, for the selection of fillers, more attention should be paid to their own characteristics, such as rich nanometer-scale pore structures, which can play the role of molecular sieves in the membrane, thereby improving the gas separation performance of the mixed matrix membrane. Or it contains active adsorption groups itself, which has a strong adsorption effect on the target separation gas, thereby generally improving the solubility of the gas to be separated in the membrane and improving its permeability. Therefore, the fillers commonly used in the preparation of mixed matrix membranes are porous zeolites, carbon molecular sieves, metal organic frameworks, and some natural porous mineral particles.
[0005] Metal-organic frameworks are formed by chelating or complexing some transition metal ions such as copper, iron, titanium and some small molecular organic substances through coordination bonds, and then interweaving with each other to form an organic-inorganic complex crystal material with regular shape and regular pore structure. Due to the large number of optional metal ligands and organic types in the preparation process, the types of metal-organic frameworks are also rich and diverse, and the number of types is huge. Common metal-organic frameworks include MOF, COF, ZIF, UIO and other types. Among them, ZIF is an imidazole-based metal coordination crystal similar to the zeolite structure, that is, the imidazole organic matter replaces the original atoms in the zeolite, and the transition metal replaces the silicon and aluminum atoms in the zeolite. Due to the similarity in structural form, the ZIF metal-organic framework has the advantages of some zeolites, with good chemical and physical stability and rich microporous structure.
[0006] Ionic liquids are organic salts that are liquid at or near room temperature. They usually have a low melting point, high thermal and chemical stability, and good solubility. Ionic liquids have weak interaction forces, such as van der Waals forces, electrostatic forces, hydrogen bonding forces, etc., which lead to adsorption between ionic liquids and gaseous molecules. Among them, electrostatic forces are one of the most important forces for ionic liquids to adsorb gas molecules. When ionic liquids have a high mutual attraction relative to gaseous molecules, ionic liquids can adsorb gaseous molecules into their interior, thereby achieving gas separation and enrichment. In addition, ionic liquids can improve their ability to adsorb CO2 by adjusting their electronic and ionic properties. For example, the introduction of functional groups with high CO2 affinity, such as carboxyl and amine groups, can effectively improve the adsorption capacity of ionic liquids for CO2. Supported ionic liquids are a composite material formed by combining ionic liquids with porous materials. It has the common advantages of ionic liquids and porous materials, which can not only improve the selective separation effect, but also effectively avoid the high viscosity problem of using ionic liquids to directly absorb CO2. Further, by loading some ionic liquids with high CO2 affinity on the metal organic framework, the membrane performance can be optimized, thereby solving the problem of low permeability of organic polymer gas separation membranes to a greater extent. Summary of the invention
[0007] The present invention aims to introduce a metal organic framework with carbon dioxide adsorption performance through a blending technology, and use ionic liquid impregnation through a post-synthesis method, combined with a hybrid zeolite imidazolate framework material, so as to improve the performance of the membrane. This method aims to address the shortcomings of existing membrane materials in terms of carbon dioxide and nitrogen selectivity, and at the same time provide a new method for preparing highly selective functionalized ZIF-7-8 mixed matrix membranes. Through this innovative preparation strategy, we can develop a new membrane material with higher selectivity and can achieve efficient separation of CO2 / N2.
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane, which is as follows:
[0009] Based on the non-solvent induced crystallization method (NSIC), the crystallization behavior of the polymer is controlled, and the crystal structure, crystallization rate and morphology of ZIF-7-8 are effectively controlled. The concentration and ratio of the ligand are controlled to obtain ZIF-7-8 nanomaterials with better performance. The synthesized hybrid zeolite imidazolate framework material (ZIF-7-8) material is immersed in an ionic liquid, and the ionic liquid with poor adhesion on the surface of the material is washed off by an ethanol aqueous solution to ensure that the ionic liquid is mainly attached to the pore cage of the nanomaterial. The ethanol solution of the functionalized ZIF-7-8 is mixed with the Pebax-1657 solution to prepare the casting liquid required for the casting film, and the mixed matrix membrane is prepared by the solvent evaporation method, and finally the ZIF-7-8 mixed matrix membrane modified by the ionic liquid is obtained.
[0010] Based on the above technical solution, the specific steps are as follows:
[0011] Step 1, benzimidazole: 2-methylimidazole: methanol in a molar ratio of 1:4-12:250-300 are fully mixed to obtain a ligand solution; zinc nitrate hexahydrate: N,N-dimethylformamide solution is fully mixed in a molar ratio of 1:120-140 to obtain a metal salt solution, the two solutions are fully mixed and stirred, transferred to a reaction bottle, reacted at room temperature for 60-68 hours, washed three times with methanol, and dried to obtain a ZIF-7-8 filler;
[0012] Step 2, the ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt and methanol are fully mixed in a mass ratio of 1:15-20 to prepare a mixed solution. The ZIF-7-8 filler obtained in step 1 is dispersed in the mixed solution, ultrasonically dispersed at 25-50°C for 30-60min, stirred at room temperature for 6-12h, then washed with 70% ethanol aqueous solution for 3 times, and then placed in a vacuum oven for drying for 18-24h to obtain functionalized ZIF-7-8;
[0013] Step 3, after mixing anhydrous ethanol and deionized water, heat them to 70-85° C. in an oil bath with stirring, then add Pebax-1657 thereto, keep stirring at 70-85° C. for 4-5 hours to completely dissolve them, and obtain a Pebax-1657 solution;
[0014] Step 4, adding the functionalized ZIF-7-8 into the Pebax-1657 solution, ultrasonically dispersing for 10 to 30 minutes, stirring at 500 r / min for 0.5 to 1 hour, to obtain a ZIF-7-8 casting solution;
[0015] Step 5: Ultrasonic degassing the ZIF-7-8 casting solution for 10 to 30 minutes, leaving it to stand for 4 to 10 minutes, pouring it onto a clean polytetrafluoroethylene plate, placing it in a constant temperature oven at 60 to 85°C and drying it for 18 to 24 hours, then placing it in a vacuum oven and evacuating it at 60 to 85°C and continuing to dry it for 18 to 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
[0016] Furthermore, the washing process in step 1 should ensure that the ligands not involved in the coordination on the solid surface are completely removed, and the supernatant of the last centrifugation is taken and the methanol supernatant is detected by infrared spectroscopy to confirm that the ligands are completely removed.
[0017] Furthermore, the molar ratio of zinc nitrate hexahydrate in the metal salt solution in step 1 to benzimidazole and 2-methylimidazole in the ligand solution is 1:0.3 to 1:3 to 3.7.
[0018] Further, the washing process in step 2 should ensure that the ionic liquid with poor adhesion to the solid surface is washed away, and the ZIF-7-8 material impregnated with the ionic liquid is dispersed in a 70% ethanol aqueous solution, allowed to stand for 5 to 10 minutes, centrifuged at 3000 to 4000 r / min for 5 to 10 minutes, and the supernatant is taken. The ethanol water supernatant is detected by infrared spectroscopy to confirm that the solution does not contain ionic liquid. Further, the volume ratio of ethanol to water in step 3 is 6 to 9:1 to 4.
[0019] Furthermore, the mass ratio of Pebax-1657 in the Pebax-1657 solution in step 3 is 1% to 5%.
[0020] Furthermore, the mass ratio of the functionalized ZIF-7-8 in step 4 to the Pebax-1657 in the Pebax-1657 solution is 1:5 to 50.
[0021] Furthermore, the method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane is characterized in that the prepared mixed matrix membrane is used for CO2 / N2 gas separation.
[0022] The present invention is a polymer matrix material with pebax-1657 as a mixed matrix membrane, and the polymer is composed of polyamide (PA) and polyether (PE). The hardness and crystal structure of PA can provide good mechanical properties, and the ether oxygen groups in PE have a strong adsorption effect on polar molecules. The selectivity and permeability of gas separation of porous materials depend on the pore size and pore connectivity. The porous structure of ZIF-8 is composed of a central cavity (1.16nm) and narrow holes (0.34nm), which has a strong screening effect for selective separation of small molecules. However, the separation effect of membrane materials based on ZIF-8 is general, which is mainly attributed to the flexibility of the ZIF-8 framework. The flexibility of the MOF framework causes the pore size to open under gas pressure, thereby adsorbing larger molecules. This phenomenon is called "gate opening" or "swinging saloon door". ZIF-7 has a smaller pore size than ZIF-8. By blending the ligands of the two materials in a certain proportion, the prepared ZIF-7-8 material has better pore size adjustability and framework flexibility, while also having the good permeability of ZIF-8 and the selectivity of ZIF-7. Compared with ZIF-8, the pore size of ZIF-7-8 material is smaller and the flexibility is increased. At the same time, the pore size change during the adsorption and desorption of CO2 is completely reversible, and the original pore structure is restored after desorption of CO2. ZIF-7-8 is synthesized by non-solvent induced crystallization. By adding a non-solvent that is incompatible with the solute (usually a solvent that has a strong interaction with the solvent) to the solution, the solubility of the solute decreases, thereby promoting its crystallization. Controlling the type and addition rate of the non-solvent can effectively control the morphology and crystal form of the crystal. Controlling the ligand concentration and ratio obtains ZIF-7-8 nanomaterials with better performance. The prepared ZIF-7-8 filler has a suitable pore size structure and a pore cage structure that is convenient for ionic liquid loading. The force formed by the electrostatic attraction between cations and anions in ionic liquids is one of the most important forces for ionic liquids to adsorb gas molecules. When ionic liquids have a higher mutual attraction with respect to gas molecules, ionic liquids can adsorb gas molecules into their interior, thereby achieving gas separation and enrichment. Ionic liquids absorb CO2 through physical interactions such as electrostatic forces, van der Waals forces, and hydrogen bonds with CO2. By introducing ionic liquids with functional groups with high CO2 affinity, large amounts of CO2 can be absorbed through chemical reactions. These functional groups form stronger chemical bonds with CO2, thereby increasing the adsorption capacity of ionic liquids for CO2. Sulfonyl imide salts themselves have strong nucleophilicity, and carbon dioxide can react with them as an electrophilic reagent. This type of reaction can be used as a way to capture carbon dioxide.The present invention introduces a metal organic framework with carbon dioxide adsorption performance through a blending technology, and uses 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt ([bmim][Tf2N]) as an ionic liquid, and functionalizes ZIF-7-8 through a post-synthesis method to further improve membrane performance. By blending the functionalized ZIF-7-8 porous filler into the Pebax-1657 solution, the prepared mixed matrix membrane can form a large number of directional transport channels for CO2 permeation in the membrane. This method not only greatly improves the selectivity of the membrane for CO2 / N2, but also the entire preparation process is gentle and simple, with relatively low cost, providing effective technical support for the large-scale separation of CO2 by mixed matrix membranes in future green development. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of ZIF-7-8 prepared in Example 1 and ZIF-8 prepared in Comparative Example 2;
[0024] Figure 2 FT-IR spectra of the pure Pebax membrane of Comparative Example 1, the ZIF-7-8Pebax mixed matrix membrane of Comparative Example 3, the functionalized ZIF-7-8Pebax mixed matrix membrane prepared by the ionic liquid [bmim][PF6] of Comparative Example 4, and the functionalized ZIF-7-8Pebax mixed matrix membrane prepared by the ionic liquid [bmim][Tf2N] of Example 2;
[0025] Figure 3 These are the performance diagrams of the pure Pebax membrane of comparative example 1, the ZIF-7-8Pebax mixed matrix membrane of comparative example 3, and the mixed matrix membrane obtained after functionalizing ZIF-7-8 with ionic liquid [bmim][Tf2N] in examples 1 to 3. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The present invention provides a method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane. Based on the non-solvent induced crystallization method (NSIC), the crystallization behavior of the polymer is controlled, and the crystal structure, crystallization rate and morphology of ZIF-7-8 are effectively controlled. A ZIF-7-8 nanomaterial with better performance is obtained. The synthesized hybrid zeolite imidazolate framework material (ZIF-7-8) material is immersed in an ionic liquid, and 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt ([bmim][Tf2N]) is selected to modify the nanomaterial to improve the CO2 adsorption performance of the material, and the ionic liquid with poor adhesion on the surface of the material is washed off by a 70% ethanol aqueous solution to ensure that the ionic liquid is mainly attached to the cavity of the material. The functionalized ZIF-7-8 is mixed with a Pebax-1657 solution to prepare a casting solution required for casting a membrane, and a mixed matrix membrane is prepared by a solvent evaporation method, and finally a ZIF-7-8 mixed matrix membrane modified with an ionic liquid is obtained.
[0028] The following is a detailed description of the method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane provided by the present invention through examples.
[0029] Embodiment 1:
[0030] Step 1, prepare pure ZIF-7-8: weigh 1.477g of ligand 2-methylimidazole and 0.236g of benzimidazole, dissolve in 50mL of methanol solution (CH3OH), then weigh 1.485g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68h, wash three times with methanol, and dry to obtain ZIF-7-8 filler;
[0031] Step 2, weigh 0.5 g of ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt ([bmim][Tf2N]) and 10 mL of methanol, mix the two thoroughly, disperse the above-obtained ZIF-7-8 in the diluted ionic liquid, ultrasonically disperse at 50°C for 60 min, then stir at room temperature for 12 h, then wash it three times with 70% ethanol aqueous solution, and place it in a vacuum oven to dry for 24 h to obtain functionalized ZIF-7-8;
[0032] Step 3, weigh 50.31 g of ethanol and 15.44 g of distilled water, mix them, heat them to 75° C. under stirring, then add 2.37 g of Pebax-1657 thereto, keep stirring at 75° C. for 5 hours to completely dissolve them, and obtain a Pebax-1657 solution;
[0033] Step 4, (mass ratio of ZIF-7-8:Pebax1657 is: 1:20) After removing impurities by centrifugation, take 6.5g Pebax-1657 solution and add 0.0113g ZIF-7-8 nanoparticles thereto, ultrasonically treat for 10min, stir at 500r / min for 30min to make it evenly dispersed, and obtain a ZIF-7-8 casting solution;
[0034] Step 5: Ultrasonic degassing the casting solution for 15 minutes, letting it stand for 5 minutes, and then pouring it into a clean polytetrafluoroethylene mold. The membrane was then placed in a constant temperature oven at 60°C and dried for 24 hours. Finally, vacuum drying was continued in a vacuum oven for 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
[0035] ZIF-7 and ZIF-8 have distinctly different crystal structures. Figure 1 As shown in the XRD patterns of ZIF-7-8 and ZIF-8 synthesized by the materials, a small amount of benzimidazole and 2-methylimidazole were added to synthesize ZIF-7-8, and the framework can still maintain the cubic structural characteristics of ZIF-8. Figure 2 As shown in the FT-IR image of the ZIF-7-8Pebax mixed matrix membrane modified with ionic liquid [bmim][Tf2N], the -1 The stretching vibration peak of the S=O bond in the sulfonyl group appears near 1150-1300 cm -1 The stretching vibration peak of the CF bond in the trifluoromethyl group appeared nearby, proving that the ionic liquid [bmim][Tf2N] was successfully loaded on ZIF-7-8.
[0036] The separation performance of the mixed matrix membrane was tested to be PCO2=63.21 Barrer and CO2 / N2 selectivity 85.73.
[0037] Embodiment 2:
[0038] Step 1, prepare pure ZIF-7-8: weigh 1.477g of ligand 2-methylimidazole and 0.236g of benzimidazole, dissolve in 50mL of methanol solution (CH3OH), then weigh 1.485g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68h, wash three times with methanol, and dry to obtain ZIF-7-8 filler;
[0039] Step 2, weigh 0.5 g of ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt ([bmim][Tf2N]) and 10 mL of methanol, mix the two thoroughly, disperse the above-obtained ZIF-7-8 in the diluted ionic liquid, ultrasonically disperse at 50°C for 60 min, then stir at room temperature for 12 h, then wash it three times with 70% ethanol aqueous solution, and place it in a vacuum oven to dry for 24 h to obtain functionalized ZIF-7-8;
[0040] Step 3, weigh 50.31 g of ethanol and 15.44 g of distilled water, mix them, heat them to 75° C. under stirring, then add 2.37 g of Pebax-1657 thereto, keep stirring at 75° C. for 5 hours to completely dissolve them, and obtain a Pebax-1657 solution;
[0041] Step 4, (ZIF-7-8: Pebax mass ratio is 1:10) After removing impurities by centrifugation, 6.5 g of Pebax-1657 solution was taken and 0.0226 g of ZIF-7-8 nanoparticles were added thereto, and ultrasonic treatment was performed for 10 min, and stirring was performed at 500 r / min for 30 min to make it evenly dispersed to obtain a ZIF-7-8 casting solution;
[0042] Step 5: Ultrasonic degassing the casting solution for 15 minutes, letting it stand for 5 minutes, and then pouring it into a clean polytetrafluoroethylene mold. The membrane was then placed in a constant temperature oven at 60°C and dried for 24 hours. Finally, vacuum drying was continued in a vacuum oven for 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
[0043] The separation performance of the mixed matrix membrane was tested to be PCO2=64.27 Barrer and CO2 / N2 selectivity 92.21.
[0044] Embodiment 3:
[0045] Step 1. Prepare pure ZIF-7-8: weigh 1.477 g of the ligand 2-methylimidazole and 0.236 g of benzimidazole, dissolve them in 50 mL of methanol solution (CH3OH), then weigh 1.485 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve it in 50 mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68 hours, wash three times with methanol, and dry to obtain ZIF-7-8 filler.
[0046] Step 2, weigh 0.5 g of ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt ([bmim][Tf2N]) and 10 mL of methanol, mix the two thoroughly, disperse the above-obtained ZIF-7-8 in the diluted ionic liquid, ultrasonically disperse at 50°C for 60 min, then stir at room temperature for 12 h, then wash it three times with 70% ethanol aqueous solution, and place it in a vacuum oven to dry for 24 h to obtain functionalized ZIF-7-8;
[0047] Step 3, weigh 50.31 g of ethanol and 15.44 g of distilled water, mix them, heat them to 75° C. under stirring, then add 2.37 g of Pebax-1657 thereto, keep stirring at 75° C. for 5 hours to completely dissolve them, and obtain a Pebax-1657 solution;
[0048] Step 4, (ZIF-7-8: Pebax mass ratio: 3:20) After removing impurities by centrifugation, take 6.5 g of Pebax-1657 solution and add 0.0339 g of ZIF-7-8 nanoparticles thereto, ultrasonically treat for 10 min, and stir at 500 r / min for 30 min to make it evenly dispersed to obtain a ZIF-7-8 casting solution;
[0049] Step 5: Ultrasonic degassing the casting solution for 15 minutes, letting it stand for 5 minutes, and then pouring it into a clean polytetrafluoroethylene mold. The membrane was then placed in a constant temperature oven at 60°C and dried for 24 hours. Finally, vacuum drying was continued in a vacuum oven for 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
[0050] The separation performance of the mixed matrix membrane was tested to be PCO2=68.13 Barrer and CO2 / N2 selectivity 82.23.
[0051] Comparative Example 1:
[0052] Step 1, preparing a casting solution: weighing 50.31 g of ethanol and 15.44 g of distilled water, mixing them, heating them to 75° C. under stirring, and then adding 2.37 g of Pebax-1657 thereto, maintaining stirring at 75° C. for 5 hours to completely dissolve the Pebax-1657 casting solution;
[0053] Step 2: After ultrasonic degassing the casting solution for 15 minutes, let it stand for 5 minutes and pour it into a clean polytetrafluoroethylene mold. Then, put the membrane into a constant temperature oven at 60°C and dry it for 24 hours. Then, continue to dry it in a vacuum oven for 24 hours. Pebax-1657 organic polymer membrane.
[0054] The separation performance of the mixed matrix membrane was tested to be PCO2=55.93 Barrer and CO2 / N2 selectivity 39.63.
[0055] Comparative Example 2:
[0056] Step 1, prepare pure ZIF-8: weigh 1.642 g of ligand 2-methylimidazole, dissolve in 50 mL of methanol solution (CH3OH), then weigh 1.485 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50 mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68 h, wash three times with methanol, and dry to obtain ZIF-8 filler;
[0057] Step 2, prepare casting solution: (mass ratio of ZIF-8:Pebax is 1:10): weigh 50.31g ethanol and 15.44g distilled water, mix them, heat them to 75°C under stirring, then add 2.37g Pebax-1657 and keep stirring at 75°C for 5 hours to completely dissolve them. After removing impurities by centrifugation, take 6.5g Pebax-1657 solution and add 0.0226g ZIF-8 nanoparticles to it, ultrasonicate for 10min and stir vigorously for 30min to make it evenly dispersed, to obtain casting solution;
[0058] Step 3: After ultrasonic degassing the casting solution for 15 minutes, let it stand for 5 minutes and pour it into a clean polytetrafluoroethylene mold. Then, place the membrane in a constant temperature oven at 60°C and dry it for 24 hours. Then, continue to dry it in a vacuum oven for 24 hours to obtain a ZIF-8 composite modified mixed matrix membrane.
[0059] The separation performance of the mixed matrix membrane was tested to be PCO2=57.63 Barrer and CO2 / N2 selectivity 64.17.
[0060] Comparative Example 3:
[0061] Step 1, prepare pure ZIF-7-8: weigh 1.477g of ligand 2-methylimidazole and 0.236g of benzimidazole, dissolve in 50mL of methanol solution (CH3OH), then weigh 1.485g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68h, wash three times with methanol, and dry to obtain ZIF-7-8 filler;
[0062] Step 2, prepare casting solution: (mass ratio of ZIF-7-8:Pebax is 1:10): weigh 50.31g ethanol and 15.44g distilled water, mix them, heat them to 75°C under stirring, then add 2.37g Pebax-1657 and keep stirring at 75°C for 5 hours to completely dissolve them. Then, remove impurities by centrifugation, take 6.5g Pebax-1657 solution, add 0.0226g ZIF-7-8 nanoparticles, ultrasonically treat for 10min, and vigorously stir for 30min to make them evenly dispersed, to obtain casting solution;
[0063] Step 3: After ultrasonic degassing the casting solution for 15 minutes, let it stand for 5 minutes and then pour it into a clean polytetrafluoroethylene mold. Then, place the membrane in a constant temperature oven at 60°C and dry it for 24 hours. Finally, continue to dry it in a vacuum oven for 24 hours to obtain a pure ZIF-7-8 composite modified mixed matrix membrane.
[0064] The separation performance of the mixed matrix membrane was tested to be PCO2=56.29 Barrer and CO2 / N2 selectivity 75.13.
[0065] Comparative Example 4:
[0066] Step 1, prepare pure ZIF-7-8: weigh 1.477g of ligand 2-methylimidazole and 0.236g of benzimidazole, dissolve in 50mL of methanol solution (CH3OH), then weigh 1.485g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68h, wash three times with methanol, and dry to obtain ZIF-7-8 filler;
[0067] Step 2, weigh 0.5 g of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6]) and 10 mL of methanol, mix the two thoroughly, disperse the above-obtained ZIF-7-8 in the diluted ionic liquid, ultrasonically disperse at 50° C. for 60 min, then stir at room temperature for 12 h, then wash the modified ZIF-7-8 with 70% ethanol aqueous solution, and dry it in a vacuum oven for 18 to 24 h to obtain [bmim][PF6] functionalized ZIF-7-8 filler;
[0068] Step 3, prepare casting solution: (mass ratio of ZIF-7-8:Pebax is 1:10): weigh 50.31g ethanol and 15.44g distilled water, mix them, heat them to 75°C under stirring, then add 2.37g Pebax-1657 and keep stirring at 75°C for 5 hours to completely dissolve them. After that, remove impurities by centrifugation, take 6.5g Pebax-1657 solution, add 0.0226g ZIF-7-8 nanoparticles, ultrasonically treat for 10min, and vigorously stir for 30min to make them evenly dispersed, to obtain casting solution;
[0069] Step 4: Ultrasonic degassing the casting solution for 15 minutes, letting it stand for 5 minutes, and then pouring it into a clean polytetrafluoroethylene mold. The membrane was then placed in a constant temperature oven at 60°C and dried for 24 hours. Finally, vacuum drying was continued in a vacuum oven for 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
[0070] like Figure 2 As shown in the FT-IR image of the ZIF-7-8Pebax mixed matrix membrane modified with ionic liquid [bmim][PF6], the -1 The PF bond stretching vibration peak appears nearby, proving that the ionic liquid [bmim][PF6] is successfully loaded on ZIF-7-8.
[0071] The separation performance of the mixed matrix membrane was tested to be PCO2=59.27 Barrer and CO2 / N2 selectivity 79.61.
[0072] Comparative Example 5:
[0073] Step 1, prepare pure ZIF-7-8: weigh 1.477g of ligand 2-methylimidazole and 0.236g of benzimidazole, dissolve in 50mL of methanol solution (CH3OH), then weigh 1.485g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), dissolve in 50mL of N,N-dimethylformamide solution (DMF), stir the two solutions thoroughly, transfer them into a reaction bottle, react at room temperature for 68h, wash three times with methanol, and dry to obtain ZIF-7-8 filler;
[0074] Step 2, prepare casting solution: (mass ratio of ZIF-7-8:Pebax is 1:10): weigh 50.31g ethanol and 15.44g distilled water, mix them, heat them to 75°C under stirring, then add 2.37g Pebax-1657 and keep stirring at 75°C for 5 hours to completely dissolve them. Then, remove impurities by centrifugation, take 6.5g Pebax-1657 solution, add 0.0226g ZIF-7-8 nanoparticles, ultrasonically treat for 10min, and vigorously stir for 30min to make them evenly dispersed, to obtain casting solution;
[0075] Step 3, after ultrasonic degassing the above casting solution for 15 minutes, let it stand for 5 minutes, and then pour it into a clean polytetrafluoroethylene mold, and then put the membrane into a constant temperature oven at 60°C for 24 hours, and finally continue to dry it in a vacuum oven for 24 hours to obtain a pure ZIF-7-8 composite modified mixed matrix membrane;
[0076] Step 4. Weigh 0.5 g of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([bmim][Tf2N]) and 10 mL of methanol, mix the two thoroughly, and place them in a glass dish. Place the ZIF-7-8 mixed matrix membrane obtained above into the prepared ionic liquid and immerse it for 24 to 48 hours. Then place it in a vacuum oven and dry it for 18 to 24 hours to obtain a ZIF-7-8 mixed matrix membrane directly impregnated with the ionic liquid.
[0077] The separation performance of the mixed matrix membrane was tested to be PCO2=68.93 Barrer and CO2 / N2 selectivity 47.21.
[0078] The relevant performance test results of the mixed matrix membranes prepared by ionic liquid-loaded modified ZIF-7-8 at different contents and Pebax-1657 in Comparative Examples 1 to 5 and Examples 1 to 3 are shown in Table 1.
[0079] Table 1
[0080]
[0081] As can be seen from Table 1, after the examples 1 to 3 of the present invention, due to the introduction of ionic liquids with high CO2 affinity functional groups, compared with the [bmim][PF6] ionic liquid impregnation in Comparative Example 4, the ionic liquid [bmim][Tf2N] impregnation has a greater improvement in the permeability and selectivity of the ZIF-7-8 mixed matrix membrane. Comparative Example 5 directly uses the ionic liquid [bmim][Tf2N] to impregnate the membrane material. Although the permeability of CO2 increases, the selectivity decreases greatly. In Example 2, the mass ratio of ZIF-7-8 to Pebax is 1:10, and after impregnation with the ionic liquid [bmim][Tf2N], it has excellent CO2 / N2 selectivity.
[0082] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane, characterized in that: The following steps are involved: Step 1, benzimidazole: 2-methylimidazole: methanol in a molar ratio of 1:4-12:250-300 are fully mixed to obtain a ligand solution; zinc nitrate hexahydrate: N,N-dimethylformamide solution is fully mixed in a molar ratio of 1:120-140 to obtain a metal salt solution, the two solutions are fully mixed and stirred, transferred to a reaction bottle, reacted at room temperature for 60-68 hours, washed three times with methanol, and dried to obtain a ZIF-7-8 filler; Step 2, the ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt and methanol are fully mixed in a mass ratio of 1:15-20 to prepare a mixed solution. The ZIF-7-8 filler obtained in step 1 is dispersed in the mixed solution, ultrasonically dispersed at 25-50°C for 30-60min, stirred at room temperature for 6-12h, then washed with 70% ethanol aqueous solution for 3 times, and then placed in a vacuum oven for drying for 18-24h to obtain functionalized ZIF-7-8; Step 3, after mixing anhydrous ethanol and deionized water, heat them to 70-85° C. in an oil bath with stirring, then add Pebax-1657 thereto, keep stirring at 70-85° C. for 4-5 hours to completely dissolve them, and obtain a Pebax-1657 solution; Step 4, adding the functionalized ZIF-7-8 into the Pebax-1657 solution, ultrasonically dispersing for 10 to 30 minutes, stirring at 500 r / min for 0.5 to 1 hour, to obtain a ZIF-7-8 casting solution; Step 5: Ultrasonic degassing the ZIF-7-8 casting solution for 10 to 30 minutes, leaving it to stand for 4 to 10 minutes, pouring it onto a clean polytetrafluoroethylene plate, placing it in a constant temperature oven at 60 to 85°C and drying it for 18 to 24 hours, then placing it in a vacuum oven and evacuating it at 60 to 85°C and continuing to dry it for 18 to 24 hours to obtain a functionalized ZIF-7-8 mixed matrix membrane.
2. The method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The washing process in step 1 should ensure that the ligands not involved in the coordination on the solid surface are completely removed. Take the supernatant of the last centrifugation and detect the methanol supernatant by infrared spectroscopy to confirm that the ligands are completely removed.
3. The method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The molar ratio of zinc nitrate hexahydrate in the metal salt solution and benzimidazole and 2-methylimidazole in the ligand solution in step 1 is 1:0.3 to 1:3 to 3.
7.
4. The method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The washing process described in step 2 should ensure that the ionic liquid with poor adhesion to the solid surface is washed away. The ZIF-7-8 material impregnated with the ionic liquid is dispersed in a 70% ethanol aqueous solution, allowed to stand for 5 to 10 minutes, centrifuged at 3000 to 4000 r / min for 5 to 10 minutes, the supernatant is taken, and the ethanol water supernatant is detected by infrared spectroscopy to confirm that the solution does not contain ionic liquid.
5. The method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The volume ratio of ethanol to water in step 3 is 6-9:1-4.
6. The method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The mass ratio of Pebax-1657 in the Pebax-1657 solution in step 3 is 1% to 5%.
7. A method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to claim 1, characterized in that: The mass ratio of the functionalized ZIF-7-8 in step 4 to the Pebax-1657 in the Pebax-1657 solution is 1:5 to 50.
8. A method for preparing a highly selective functionalized ZIF-7-8 mixed matrix membrane according to any one of claims 1 to 7, characterized in that: The prepared mixed matrix membrane is used for CO2 / N2 gas separation.
Citation Information
Patent Citations
Preparation method of mixed matrix membrane for accurately screening gas molecule pairs
CN110639373A
Preparation method of ZIF-7-8 zeolite imidazate framework material with polyhedral mutual embedded morphology
CN113429578A
Flexible metal organic framework material as well as preparation method and application thereof
CN116328730A
Preparation and application of high-performance mixed matrix gas separation membrane based on ionic liquid coordination
CN116351265A
Cited By
Gas separation membrane with semi-interpenetrating network structure as well as preparation method and application of gas separation membrane
CN121588656A